Penerapan Algoritma Greedy Pada Pengaturan Shipping Buku Diknas PT. X - Wiratama, Stefani Gisella; Christian, Christian; Johanna, Felita; Gonardi, Jesslyn; Purnomo, Kevin (School of Industrial and System Engineering, Telkom University, 2018)
PT. X is a company engaged in manufacturing media printing and paper packaging. PT. X has a fixed product that is a Diknas book. The research is focused on the delivery of Diknas book for East Java region with a total time as the main constrain in determining the route which resulted in the minimum delivery cost of Diknas book by taking into account the capacity of the fleet used. The method used in determining the route with the optimal shipping cost is by the Greedy Algorithm method. Research shows that in zone 1 there are 4 shipping routes with range of shipping cost between Rp100,00/kg-Rp200,00/kg by using joint route, zone 2 there are 3 delivery routes with range of shipping cost between Rp190,00/kg-Rp205,00/kg, zone 3 there are 3 shipping routes with a range of shipping costs between Rp130,00/kg-Rp525,00/kg, zone 2 and zone 3 using separate route method and joint route.